DEVELOPMENT OF ENTREPRENEURSHIP ON THE BASIS OF PERSONAL PEASANT FARMS, AS A MEANS OF IMPROVING THE QUALITY COMPONENT OF HUMAN CAPITAL OF AGRICULTURAL - Varchenko , O.M.; Swinous , I.V.; Ponedilchuk , T.V. (The actual problems of regional economy development, 2020)
The article is aimed at studying the problems of development on the basis of personal farms as a means of improving the quality component of human capital in rural areas. The purpose of the study is to calculate the forecast values ​​of highly marketable personal farms for the development of practical recommendations for state and regional support measures that create on their basis small businesses in the field of agribusiness as a quality component of human capital in rural areas. The theoretical and methodological basis of the study were: dialectical method of cognition of socio-economic phenomena, fundamental research of domestic and foreign scientists on the functioning of personal farms, rural community, In the process of research, generally accepted methods and techniques were used: a set of scientific methods of abstract-logical method (induction and deduction, analysis and synthesis, analogies and comparisons, formalizations and modeling) - to study the theoretical principles of organizational and economic foundations of personal farms and small sub objects of entrepreneurial activity in the field of agribusiness; monographic - to clarify the problems of transformation of OSG into farms, the method of questionnaires - to determine the intentions of the heads of personal farms, the development on their basis of small businesses in the field of agribusiness, the method of observations - to clarify certain aspects of OSG . Theoretical and applied aspects of the transformation of personal farms into the formation of entrepreneurial type in the field of agribusiness by creating favorable socio-economic conditions for their development are revealed. It is established that the lack of effective support from state and local authorities regarding the development and functioning of small-scale production on the basis of private farms leads to negative processes, which are manifested in the transformation of farms into private farms. The directions of strengthening the state support for the development of OSG are substantiated.